2021
DOI: 10.3389/fimmu.2021.721975
|View full text |Cite
|
Sign up to set email alerts
|

HBV-Specific CD8+ T-Cell Tolerance in the Liver

Abstract: Hepatitis B virus (HBV) remains a leading cause of liver-related morbidity and mortality through chronic hepatitis that may progress to liver cirrhosis and cancer. The central role played by HBV-specific CD8+ T cells in the clearance of acute HBV infection, and HBV-related liver injury is now well established. Vigorous, multifunctional CD8+ T cell responses are usually induced in most adult-onset HBV infections, while chronic hepatitis B (CHB) is characterized by quantitatively and qualitatively weak HBV-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 83 publications
0
37
0
Order By: Relevance
“…During HBV infection, both the number and fitness of HBV-specific T and B lymphocytes increase significantly [ 47 , 48 , 49 ]. The indispensable role played by HBV-specific CD8 + T cells in the clearance of HBV has been well recognized [ 38 , 48 , 50 , 51 , 52 , 53 ]. Moreover, CD4 + T cells are required to promote the activation and function of these CD8 + T cells.…”
Section: Mechanisms Of Hbv Immune Evasionmentioning
confidence: 99%
“…During HBV infection, both the number and fitness of HBV-specific T and B lymphocytes increase significantly [ 47 , 48 , 49 ]. The indispensable role played by HBV-specific CD8 + T cells in the clearance of HBV has been well recognized [ 38 , 48 , 50 , 51 , 52 , 53 ]. Moreover, CD4 + T cells are required to promote the activation and function of these CD8 + T cells.…”
Section: Mechanisms Of Hbv Immune Evasionmentioning
confidence: 99%
“…High-level antigen expression has been identified as a key factor in reducing the efficacy of effector T cell responses [88,106] and has been suspected to play a role in attenuating HBV-specific immunity during chronic infection [95,106,107]. Recently, we have demonstrated that reduction of HBV-replication and gene expression through an siRNA or shRNA approach before therapeutic vaccination in two different models of persistent HBV infection in mice increased the efficacy of therapeutic vaccination, to eliminate HBV-expressing hepatocytes and achieve control of persistent infection [59].…”
Section: Local Support For T Cell Immunity In the Liver To Increase E...mentioning
confidence: 99%
“…HBV-specific CD8 + T cells are pivotal in antiviral activity either by indirectly secreting cytokines, such as IFN-γ and TNF-α, or directly killing HBV infected hepatocytes, but their response is weak in chronic hepatitis B (CHB) patients exhibiting immune tolerance ( 7 ). Recently, evidence showed that mMDSCs cross-presenting HBsAg migrated to the thymus and selectively deleted HBsAg-specific CD8 + thymocytes in infants and young patients, resulting in CD8 + T cell tolerance and HBV persistence ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous HBV core-specific and HBV polymerase-specific CD8 + T cells with polyfunctionality and long-term memory were detected in chronic HBV-infected patients ( 10 12 ). Conversely, HBV-specific CD8 + T cells were demonstrated to be exhausted CD8 + T cells, exhibiting several kinds of inhibitory receptors such as PD-1, CTLA-4, Tim-3, and TIGIT in chronic HBV infection ( 7 , 13 15 ). Additionally, HBV antigen-presentation by intrahepatic APCs with weakened costimulatory signals also contributed to peripheral tolerance of HBV-specific CD8 + T cells during chronic HBV infection ( 15 ).…”
Section: Introductionmentioning
confidence: 99%